Body image and its relationship to self-esteem among pregnant women in the light of some demographic variables - Alshehri, Atheer Ali (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the body image and its relationship to the self- esteem of the pregnant woman in the light of some demographic variables (age, economic educational level, stage of pregnancy, number of pregnancies). a pregnant woman, and the body image scale (Kirk, Preston, 2019) was applied, Arabizing the researcher, and Rosenberg’s Self- Esteem Scale Arabization (Jaradat, 2006).And the results resulted in a negative, statistically significant correlation at the level of significance (0, 01), between the body image of the pregnant woman (in the sub- dimensions and in the total degree) and self- esteem, and there are no statistically significant differences in the body image of the pregnant woman according to the different demographic variables (age, education level, number of pregnancies, and stage of pregnancy).In While there were differences in the socio- economic level in favor of the low level, and there were no statistically significant differences in the self- esteem of the pregnant woman according to the different demographic variables (age, education level, number of pregnancies, and stage of pregnancy), however, there may be statistically significant differences At a significance level of (0.01) in self- esteem according to the variable (economic and social level), in favor of those with an economic and social level (high), and among those with an economic and social level (low and medium), in favor of those with an economic and social level (medium(.The study recommends paying attention to improving women's self- esteem during pregnancy by providing counseling services by health care providers in clinics and identifying women who have low risk factors for self- esteem; Because of its negative impact on them, enhancing self- social support and psychological resilience of pregnant women.
Keywords: body image; self- esteem; pregnant women